2013
DOI: 10.1517/14712598.2013.849690
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells as a potential therapy for necrotizing enterocolitis

Abstract: The current data are promising and demonstrate that stem cells do have an effect in rodent models of NEC. However, the short timescale, limited ability for longitudinal evaluation and uncertain clinical relevance of these models means that there are considerable challenges to be overcome before attempting stem cell therapy in clinical trials. Nevertheless, these data open up novel areas of research into a prevention or therapy for this devastating disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Four SC were compared: (1) amniotic fluid-derived mesenchymal SC (AF-MSC); (2) amniotic fluid-derived neural SC (AF-NSC); (3) bone marrow-derived mesenchymal SC (BM-MSC); and (4) neonatal enteric neural SC (E-NSC). Using an established rat model of NEC, pups delivered prematurely received an intraperitoneal injection of SC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four SC were compared: (1) amniotic fluid-derived mesenchymal SC (AF-MSC); (2) amniotic fluid-derived neural SC (AF-NSC); (3) bone marrow-derived mesenchymal SC (BM-MSC); and (4) neonatal enteric neural SC (E-NSC). Using an established rat model of NEC, pups delivered prematurely received an intraperitoneal injection of SC.…”
Section: Methodsmentioning
confidence: 99%
“…The model of NEC was based on that described by Barlow et al . (6, 7, 2023) Rat pups delivered via C-section one half-day prematurely were randomized into six groups: (1) breastfed ( n = 10 ); (2) NEC + 1% phosphate-buffered saline (PBS, Corning, Manassas, VA) ( n = 62 ); (3) NEC + AF-MSC ( n = 42 ); (4) NEC + AF-NSC ( n = 37 ); (5) NEC + BM-MSC ( n = 48 ); (6) NEC + E-NSC ( n = 36 ). After delivery, each pup received a single intraperitoneal (IP) injection of 2×10 6 SC in 0.1mL PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence from 3 different research groups has suggested that stem cells are able to influence the course of the disease in experimental NEC [88]: amniotic fluid stem (AFS) cells [89], mesenchymal stem cells [90,91], and enteric neural stem system cells [92]. In addition to the beneficial effects of AFS cells and the conditioned medium from AFS cells, other recent evidence highlights the potential role of factors in amniotic fluid in the prevention and/or treatment of NEC.…”
Section: Preventionmentioning
confidence: 99%
“…Researchers in the field of experimental NEC have demonstrated that stem cells are beneficial in therapy for this condition [3,5,20,21]. The question remains as to how these cells are workingwhether it is by paracrine effects or by integration into the damaged tissue with regeneration.…”
Section: Discussionmentioning
confidence: 99%